2019
DOI: 10.1021/acs.jmedchem.9b01034
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AM-6494: A Potent and Orally Efficacious β-Site Amyloid Precursor Protein Cleaving Enzyme 1 (BACE1) Inhibitor with in Vivo Selectivity over BACE2

Abstract: β-Site amyloid precursor protein cleaving enzyme 1 (BACE1) is an aspartyl protease that plays a key role in the production of amyloid β (Aβ) in the brain and has been extensively pursued as a target for the treatment of Alzheimer's disease (AD). BACE2, an aspartyl protease that is structurally related to BACE1, has been recently reported to be involved in melanosome maturation and pigmentation. Herein, we describe the development of a series of cyclopropylthiazines as potent and orally efficacious BACE1 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Because of the important role of BACE1 as a target in the treatment of AD, experimental studies are increasingly focused on the determination of inhibitor–BACE1 complex structures and the development of inhibitors that interrupt the cleavage of APP by BACE1 for use in the clinic; , these studies will provide rich structural bases for the design of drugs that target BACE1. Through these experimental studies, the alterations and effect of the environmental pH, which certainly disrupts the activity of BACE1, have been described .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the important role of BACE1 as a target in the treatment of AD, experimental studies are increasingly focused on the determination of inhibitor–BACE1 complex structures and the development of inhibitors that interrupt the cleavage of APP by BACE1 for use in the clinic; , these studies will provide rich structural bases for the design of drugs that target BACE1. Through these experimental studies, the alterations and effect of the environmental pH, which certainly disrupts the activity of BACE1, have been described .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing interest in the development of small, non-peptide inhibitors of the β-amyloid cleaving enzyme 1 (BACE-1, β-secretase) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], following the suggestion that this enzyme may be involved in the pathogenesis of Alzheimer’s Disease (AD) [ 19 , 25 ]. BACE-1 is an aspartyl protease involved in the proteolytic degradation of the β-amyloid precursor protein (APP) to form amyloid-β peptide (Aβ), a small protein with a high tendency to form aggregates that are found in the AD brain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…After designing more than 20 substituents ( Figure 3) of different functional units attached in an N‐methylation pattern to the rivastigmine, we use two web‐based software to filter these derivatives. The N‐substitution premise on a recent study [57] where we modified the scissile bond strength of a newly identified beta‐secretase inhibitor [58] for improved affinity. Selective N‐methylation of amide nitrogen atoms increases the proteolytic stability/bioavailability of peptides [59] .…”
Section: Methodsmentioning
confidence: 99%